Investigation of sewing and water repellent performance of outdoor clothing. Issue 5 (2nd September 2019) - Erayman Yüksel, Yaşar; Korkmaz, Yasemin
Abstract : Purpose: Durability of textile materials under wet conditions has become very important in recent years. The water repellency performance of fabrics should be maintained in the seam areas. The purpose of this paper is to analyze the effect of water repellent agents and sewing threads on the seam and water repellency performance properties of woven fabrics. Design/methodology/approach: 100 percent polyester woven fabrics were treated with three different water repellent finishing agents (silicone, fluorocarbons with 6 and 8 carbons) and then sewn with different sewing threads (unfinished/water repellent finished polyester/cotton corespun and polyamide filament). Afterwards, mechanical properties, seam performance and water repellency properties of these materials were measured. Findings: The effect of finishing which was statistically significant on seam strength only in warp direction was significant on seam elongation and efficiency in both warp and weft directions. Seam strength, seam efficiency, seam slippage and seam pucker of fabrics sewn with polyamide threads were higher than others. The fluorocarbons applied to the fabrics gave higher water repellency values than silicones. In addition, as the chain length increased in fluorocarbons, water repellency performance increased. Sewing process reduced water resistance of fabrics; however, water repellent finish applied to the threads increased water resistance of fabrics. Originality/value: As a result of the literature review, it was seen that water repellency property of a wear were studied in only seamless areas of fabrics. Originality of this study is that the water repellency properties are also analyzed in the seam areas of the fabrics and evaluated together with the seam performance characteristics.